2021
DOI: 10.32585/bjas.v3i1.1327
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic Quality of Salted Quail Eggs Using Boiled Salt From Brebes

Abstract: Salted eggs are one of the popular products and are liked by the people of Indonesia. Processing salted quail eggs is an effort for preservation, in addition to improving the taste of quail eggs This study aims to determine the organoleptic quality of quail eggs salted with fine boiled salt with a concentration of 20% (w/w) and 30% (w/w). The incubation time for the salting process is 4 days. organoleptic test with 60 untrained panellists. Yolk colour quality produces a slightly yellow colour (p>0.05). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Proses ini membutuhkan pengaturan garam yang tepat agar telur tidak terlalu asin atau basah (Hasdar et al, 2021). elur asin puyuh dapat bertahan lebih lama daripada telur puyuh segar karena proses pengasinan menghambat pertumbuhan mikroba.…”
Section: Pendahuluanunclassified
“…Proses ini membutuhkan pengaturan garam yang tepat agar telur tidak terlalu asin atau basah (Hasdar et al, 2021). elur asin puyuh dapat bertahan lebih lama daripada telur puyuh segar karena proses pengasinan menghambat pertumbuhan mikroba.…”
Section: Pendahuluanunclassified
“…Producers of quail eggs in Benin lose more than 1,688,740 eggs/year, a loss rate of 13.06% [ 2 ]. Eggs kept for more than two weeks in an open space lose their quality through breakage or cracks and the infestation of microorganisms within them [ 3 ]. According to the Institut Français d'Eveil Sanitaire (InAS), the pathogenic microorganisms responsible for Collective Foodborne Toxi-Infections (CFTI), for which eggs and egg products are compromised, are Salmonella (85.9%), Staphylococcus aureus (7%), Clostridium perfringens (2.3%), and other agents (4.4%) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To limit the risks of damage and contamination related to the fragility of their shells, several studies have been conducted to make concrete proposals to boost the practice of conservation of quail eggs. Hasdar et al [ 3 ] revealed that quail eggs can be preserved by boiling them in water containing salt at a concentration of 30%. This technique does not guarantee a long shelf life of reusable quail eggs as an ingredient.…”
Section: Introductionmentioning
confidence: 99%